Towards a Sharia Derivatives Law: Harmonizing Religious Fatwas and Financial Regulation in Indonesia - Chandra yusuf; Nurul Huda; Perdana Wahyu Santosa; Iskandar Muda (Universitas Islam Negeri Jakarta, 2026)
This article examines the legal status of sharia-compliant derivative instruments in Indonesia by analysing the relationship between DSN-MUI Fatwa No. 96/DSN-MUI/IV/2015 and the positive legal framework governing Islamic finance. Although the fatwa permits sharia hedging for genuine risk-management purposes, its legal force remains institutionally incomplete because it has not been fully translated into binding statutory or regulatory instruments. Drawing on normative legal research and a comparative analysis of Malaysia, Pakistan, and the United Arab Emirates, this article develops a Sharia-Institutional Conformity framework. The framework argues that effective harmonisation requires the simultaneous satisfaction of two conditions: substantive sharia compliance and institutional legal certainty. The Indonesian case shows that the first condition has been substantially met through the DSN-MUI fatwa authority. In contrast, the second remains underdeveloped due to fragmented regulatory integration among DSN-MUI, OJK, Bank Indonesia, and legislative institutions. The article contributes to Islamic financial law by reframing the fatwa-law gap not merely as a problem of regulatory absence, but as a structural failure of institutional translation. It recommends a phased harmonisation model consisting of technical implementing regulations, strengthened cross-agency coordination, and ultimately a Sharia Financial Products Law or dedicated Sharia Derivatives Law. Abstrak Artikel ini mengkaji status hukum instrumen derivatif syariah di Indonesia dengan menganalisis hubungan antara Fatwa DSN-MUI No. 96/DSN-MUI/IV/2015 dan kerangka hukum positif yang mengatur keuangan syariah. Meskipun fatwa tersebut memperbolehkan lindung nilai syariah untuk kebutuhan manajemen risiko yang nyata, kekuatan hukumnya masih belum lengkap secara institusional karena belum sepenuhnya diterjemahkan ke dalam instrumen peraturan yang mengikat. Dengan menggunakan penelitian hukum normatif dan analisis perbandingan terhadap Malaysia, Pakistan, dan Uni Emirat Arab, artikel ini mengembangkan kerangka Sharia-Institutional Conformity. Kerangka ini berargumen bahwa harmonisasi yang efektif mensyaratkan pemenuhan dua kondisi secara simultan: kepatuhan substantif terhadap syariah dan kepastian hukum institusional. Kasus Indonesia menunjukkan bahwa kondisi pertama telah relatif terpenuhi melalui otoritas fatwa DSN-MUI, sedangkan kondisi kedua masih belum memadai karena integrasi regulasi antara DSN-MUI, OJK, Bank Indonesia, dan lembaga legislatif masih terfragmentasi. Artikel ini berkontribusi pada hukum keuangan Islam dengan membingkai kesenjangan antara fatwa dan hukum bukan sekadar sebagai ketiadaan regulasi, melainkan sebagai kegagalan struktural dalam penerjemahan institusional. Artikel ini merekomendasikan model harmonisasi bertahap melalui peraturan teknis, koordinasi lintas lembaga, dan pembentukan Undang-Undang Produk Keuangan Syariah atau Undang-Undang Derivatif Syariah.